Development of 3D city model applying cadastral information - Žiūrienė, Rytė; Mešliūtė, Rimantė; Makutėnienė, Daiva (Geodesy and Cartography, 2012)
Problems of development of 3D city models are analysed. To develop such kind of model a great amount of information has to be computed. Collecting and matching the initial data is the most time and labour consuming job. Therefore first of all we have tried to investigate such a data source that would comprise the biggest part of needed data. We also have been looking for the data source that enabled us to constantly refresh and present the data describing the real or true to life situation. We have analysed the possibilities of city cadastral information system and here we state that it is suitable for that purpose. This article presents the idea how 3D city model consisting of prismatic building block models could be developed with the help of available cadastral information. Miesto 3D modelio kūrimas taikant kadastro informaciją Santrauka. Nagrinėjamos miesto erdvinio modelio kūrimo problemos. Kuriant tokį modelį reikia apdoroti labai didelius informacijos kiekius. Daugiausia laiko ir jėgų įdedama pradiniams duomenims surinkti ir suderinti tarpusavyje. Del šios priežasties pirmiausia buvo ieškoma tokio duomenu šaltinio, kuriame jau būtu sukaupta didesnė dalis reikalingų duomenų. Pradinių duomenų šaltiniui buvo keliamas patikimumo reikalavimas. Straipsnyje pateikiama idėją, kaip miesto 3D modelis gali būti kuriamas taikant kadastro informaciją. First published online: 03 Aug 2012